The Role Of Influencer "KOL" (Key Opinion Leader) In Influenceing Purchasing Decisions At PT. Ayo Menebar Kebaikan - Muhammad Hafidz Sudibya; Anas Hidayat (International Journal of Education, Vocational and Social Science, 2024)
This study aims to examine the role of influencers in influencing purchasing decisions at PT Ayo Menebar Kebaikan. This research is based on the phenomenon of using influencers as a marketing strategy in a certain period. This study uses a qualitative approach with data collection methods through interviews with analysis units and direct observation in the field conducted through an internship process. The results of the findings from this study are that it can be concluded that the indicators to measure the success of influencers in promoting products are that the audience is influenced by influencers and makes product purchases. Referring to this, the marketing strategy using influencers implemented by the company has proven effective in increasing product sales.